2019
DOI: 10.1007/s13205-018-1566-7
|View full text |Cite
|
Sign up to set email alerts
|

Selecting better diagnostic kits for diagnosis of malarial parasites at point of care

Abstract: Malaria is a fatal life-threatening parasitic infection and a leading cause of morbidity and mortality. The present study was aimed to evaluate simple, inexpensive, accurate, reliable, easily available better diagnostic for rapid detection of malaria at point of care (POC). The study includes 1403 samples collected from the patients, of which 1227 were clinically suspected cases and 176 from consecutive feverish patients. Among the suspected cases only 338 samples were confirmed positive and 889 samples were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Overall the microscopy and malaria antigen-based lateral flow assay exhibited similar sensitivity, specificity, PPV, NPV and efficiency; their results are comparable with our study. 13 A study in Kenya conducted in 2016 showed that in comparison to microscopy, the sensitivity of eight RDTs to detect malaria parasites was 90.3-94.8 %, and the specificity was 73.3-79.3 %. 14 Ojurongbe et al, compared PCR, thick film microscopy and RDTs to detect Malarial parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Overall the microscopy and malaria antigen-based lateral flow assay exhibited similar sensitivity, specificity, PPV, NPV and efficiency; their results are comparable with our study. 13 A study in Kenya conducted in 2016 showed that in comparison to microscopy, the sensitivity of eight RDTs to detect malaria parasites was 90.3-94.8 %, and the specificity was 73.3-79.3 %. 14 Ojurongbe et al, compared PCR, thick film microscopy and RDTs to detect Malarial parasites.…”
Section: Discussionmentioning
confidence: 99%